Homoclinic tangencies versus uniform hyperbolicity for conservative 3-flows - Bessa, Mário (2009)
We prove that a volume-preserving three-dimensional flow can be C 1 -approximated by a volume-preserving Anosov flow or else by another volume-preserving flow exhibiting a homoclinic tangency. This proves the conjecture of Palis for conservative 3-flows and with respect to the C1-topology.